2006
DOI: 10.1111/j.1600-0420.2006.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Human secretory phospholipase A2, group IB in normal eyes and in eye diseases

Abstract: ABSTRACT.Purpose: Secretory phospholipases A 2 (sPLA 2 ) are enzymes involved in lipid turnover. We recently identified sPLA 2 group IB (GIB) in the rat retina as well as in cerebral neurons and found upregulation to occur in response to light damage and seizures, respectively. The purpose of the present study was to identify human GIB (hGIB) in the normal human eye and investigate the pattern of expression in patients with eye diseases involving hGIB-rich cells. Methods: Human GIB mRNA was identified in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A reduction in phospholipid turnover observed by loss of labelling for GIB (secretory phospholipase A2 group 1B) indicating loss of endothelial function was noted in FECD endothelium (Kolko et al, 2007). Clusterin induced cell aggregation protects cells against injury by decreasing the amount of accessible cell membrane and maintaining cellecell contact; Clusterin labelling follows a distinct pattern in FECD with enhanced intracellular staining and dense staining around guttae and in the nuclei of endothelial cells; therefore it is suggested that clusterin induces endothelial cell aggregation in response to stress conditions (Jurkunas et al, 2008).…”
Section: Hernandezmentioning
confidence: 95%
“…A reduction in phospholipid turnover observed by loss of labelling for GIB (secretory phospholipase A2 group 1B) indicating loss of endothelial function was noted in FECD endothelium (Kolko et al, 2007). Clusterin induced cell aggregation protects cells against injury by decreasing the amount of accessible cell membrane and maintaining cellecell contact; Clusterin labelling follows a distinct pattern in FECD with enhanced intracellular staining and dense staining around guttae and in the nuclei of endothelial cells; therefore it is suggested that clusterin induces endothelial cell aggregation in response to stress conditions (Jurkunas et al, 2008).…”
Section: Hernandezmentioning
confidence: 95%
“…sPLA2-IB is also highly expressed in the stomach and is present at lower levels in lung, spleen, liver, colon and eyes [7-9]. Receptors for this enzyme have been identified in various tissues, and group IB PLA2 is now reported to play a role in cell proliferation and hormone release via these receptors in non-digestive tissues [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A recent report also pointed to the linkage between hG1B and ophthalmic diseases (6). Therefore, hG1B is considered to be a potential target for treatment of obesity, diabetes (4,5), or ophthalmic diseases (6).…”
mentioning
confidence: 99%